Diabetes in spotlight: current knowledge and perspectives of photobiomodulation utilization - Perrier, Quentin; Moro, Cécile; Lablanche, Sandrine (Frontiers in Endocrinology, 2024)
Diabetes is a global health concern characterized by chronic hyperglycaemia resulting from insulinopenia and/or insulin resistance. The rising prevalence of diabetes and its associated complications (ulcers, periodontitis, healing of bone healingdefect, neuropathy, retinopathy, cardiopathy and nephropathy) necessitate innovative therapeutic approaches. Photobiomodulation (PBM), involves exposing tissues and cells to low-energy light radiation, leading to biological effects, largely via mitochondrial activation. Methods. This review evaluates preclinical and clinical studies exploring the potential of PBM in diabetes and its complications, as well all clinical trials, both planned and completed, available on ClinicalTrials database. Results. This review highlights the variability in PBM parameters across studies, hindering consensus on optimal protocols. Standardization of treatment parameters and rigorous clinical trials are needed to unlock PBM''s full therapeutic potential. 87 clinical trials were identified that investigated PBM in diabetes mellitus (with 5,837 patients planned to be treated with PBM). Clinical trials assessing PBM effects on diabetic neuropathy revealed pain reduction and potential quality of life improvement. Studies focusing on wound healing indicated encouraging results, with PBM enhancing angiogenesis, fibroblast proliferation, and collagen density. PBM''s impact on diabetic retinopathy remains inconclusive however, requiring further investigation. In glycaemic control, PBM exhibits positive effects on metabolic parameters, including glucose tolerance and insulin resistance. Conclusion. Clinical studies have reported PBM-induced reductions in fasting and postprandial glycemia without an increased hypoglycaemic risk. This impact of PBM may be related to its effects on the beta cells and islets in the pancreas. Notwithstanding challenges, PBM emerges as a promising adjunctive therapy for managing diabetic neuropathy, wound healing, and glycaemic control. Further investigation into its impact on diabetic retinopathy and muscle recovery is warranted.